The effect of operating room design and behavior of operating room staff on surgical site infection (881) incidence - Iwan Dwiprahasto, Yulianto Widodo (Universitas Gadjah Mada, 2009)
Introduction: In surgery, medical error is often related to surgical site infection (551).Santa Maria Hospital, Pemalang, is a private hospital which gives priority to quality and applies the patient safety principle. During 2006, there were 7 cases of 551 in 785 surgical cases in Santa Maria Hospital, Pemalang, but this number was considered as the tip of an iceberg. The high microorganism rate, operating room design which was not agreeable with the standard by Kepmenkes No 1204/MENKES/SK/X/2004, and the behavior of operating room staff were the risk factors of 55!. ObJective:To find out the effect of the change in operating room design and behavior of operating room staff on 551 incidence in Santa Maria, Pemalang, and to find out the risk factors of 55!. Method: It was a quasi-experimental study with pre- and post-test without control group design. Population were all operating room staff, while subject of this study was operating room design. Dependent variable was 551incidence, while independent variables were behavior of operating staff and operating room design. Data were analyzed with independent t-test, chi-square test, and multivariate logistic regression. Re.ult: The change in operating room design and operating room staff behavior has significantly decreased the incidence of 551 (OR = 3.646; 95%CI = 1.24 < OR< 10.77). Conclu.lon: Intervention on operating room design and staff behavior has decreased the incidence of 55!. Risk factors of 551were operating room design, operating room staff behavior, and duration of surgery.